MRNA expression profiles of colorectal liver metastases as a novel biomarker for early recurrence after partial hepatectomy. Issue 10 (20th September 2016) - van der Stok, E.P.; Smid, M.; Sieuwerts, A.M.; Vermeulen, P.B.; Sleijfer, S.; Ayez, N.; Grünhagen, D.J.; Martens, J.W.M.; Verhoef, C.
Abstract: Background: Identification of specific risk groups for recurrence after surgery for isolated colorectal liver metastases (CRLM) remains challenging due to the heterogeneity of the disease. Classical clinicopathologic parameters have limited prognostic value. The aim of this study was to identify a gene expression signature measured in CRLM discriminating early from late recurrence after partial hepatectomy. Methods: CRLM from two patient groups were collected: I) with recurrent disease ≤12 months after surgery (N = 33), and II) without recurrences and disease free for ≥36 months (N = 30). The patients were clinically homogeneous; all had a low clinical risk score (0–2) and did not receive (neo‐) adjuvant chemotherapy. Total RNA was hybridised to Illumina arrays, and processed for analysis. A leave‐one‐out cross validation (LOOCV) analysis was performed to identify a prognostic gene expression signature. Results: LOOCV yielded an 11‐gene profile with prognostic value in relation to recurrent disease ≤12 months after partial hepatectomy. This signature had a sensitivity of 81.8%, with a specificity of 66.7% for predicting recurrences (≤12 months) versus no recurrences for at least 36 months after surgery (X2 P < 0.0001). Conclusion: The current study yielded an 11‐gene signature at mRNA level in CRLM discriminating early from late or no relapse after partial hepatectomy. Highlights: An 11‐gene expression profile was identified in colorectal liver metastases. This profile discriminates between early and no or late recurrences after liver surgery. The 11‐gene expression profile needs validation.